Neuroimaging and Neurolaw: Drawing the Future of Aging - Tigano, Vincenzo; Cascini, Giuseppe Lucio; Sanchez-Castañeda, Cristina; Péran, Patrice; Sabatini, Umberto (Frontiers in Endocrinology, 2019)
Human brain-ageing is a complex, multidimensional phenomenon. Knowledge of the numerous aspects that revolve around it is therefore essential if not only the medical issues, but also the social, psychological and legal issues related to this phenomenon are to be managed correctly. In the coming decades, it will be necessary to find solutions to the management of the progressive ageing of the population so as to increase the number of individuals that achieve successful ageing. The aim of this article is to provide a current overview of the physiopathology of brain ageing and of the role and perspectives of neuroimaging in this context. The development of neuroimaging has opened new perspectives in clinical and basic research and it has modified the concept of brain ageing. Neuroimaging will play an increasingly important role in the definition of the individual's brain ageing in every phase of the physiological and pathological process. However, when the process involved in age-related brain cognitive diseases is being investigated, factors that might affect this process on a clinical and behavioral level (genetic susceptibility, risks factors, endocrine changes) cannot be ignored but must, on the contrary, be integrated into a neuroimaging evaluation to ensure a correct and global management, and they are therefore discussed in this article. Neuroimaging appears important to the correct management of age-related brain cognitive diseases not only within a medical perspective, but also legal, according to a wider approach based on development of relationship between neuroscience and law. The term neurolaw, the neologism born from the relationship between these two disciplines, is an emerging field of study, that deals with various issues in the impact of neurosciences on individual rights. Neuroimaging, enhancing the detection of physiological and pathological brain ageing, could give an important contribution to the field of neurolaw in elderly where the full control of cognitive and volitional functions is necessary to maintain a whole series of rights linked to legal capacity. For this reason, in order to provide the clinician and researcher with a broad view of the brain-ageing process, the role of neurolaw will be introduced into the brain-ageing context.